Use of behavioural change taxonomies in systematic reviews and meta‐analyses regarding obesity management. Issue 1 (14th December 2022) - Okonya, Ochije; Siddiqui, Bilal; George, David; Fugate, Colony; Hartwell, Micah; Vassar, Matt
Summary: We investigated the prevalence of behavioural change taxonomies in systematic reviews and meta‐analyses related to obesity management. In addition, we analysed the funding sources, author conflicts of interest statements, risk of bias, and favorability of the results in such studies to determine if there was a relationship between methodological quality and taxonomy use. We searched several databases including MEDLINE, Epistemonikos, Cochrane EDSR, Pubmed and Embase for systematic reviews and meta‐analyses regarding the behavioural treatment of obesity. Screening and data extraction was performed in a masked, duplicate fashion. We performed statistical analyses to determine any significant association between use of taxonomy and study characteristics. Fifteen (of 186; 8.06%) systematic reviews used a taxonomy—nine used the BCTTv1, three used OXFAB, two used the CALO‐RE and one used "Taxonomy of choice architecture techniques." Most interventions that referenced a taxonomy were self‐mediated (6/60, 10%). Behavioural change taxonomies were mentioned in 10 (of 87, 11.49%) studies with a public funding source. Of the studies with favourable results, 14 studies (of 181, 7.73%) referred to a taxonomy. We found no statistically significant relationships between use of taxonomy and study characteristics. We found that systematic reviews regarding the management of obesity rarely mention a behavioural change taxonomy. Given the global burden of obesity, it is crucial that behavioural change techniques are reproducible and translatable. We recommend that researchers look further into how taxonomies affect the quality and reproducibility of behavioural interventions in an effort to improve patient outcomes.